Collection development and standards for protected area libraries a collection assessment of NIPA-CPPAP Library - Lim, Judy Joanne R. (2002)
NIPA Incorporated is a consortium of leading Philippine civil society organizations involved in environmental and developmental work and it has evolved as a premier organization on protected area management in the Philippines. It is a recipient of 20 million dollar grant from the Global Environmental Facility (GEP) and works with the Department of Environment and Natural Resources (DENR) and the World Bank in the implementation of the Conservation of Priority protected Areas Project (CPPAP) that pilot tests that NIPAS' Law. The CPPAP has a time frame of 7 years (1994-2001) and ten sites are selected based on their biogeographic location biodiversity importance, funding needs and legal status as a conservation area.